Autonomous learning and creative cognition: the mediating effect of gifted students’ self-efficacy - Orakcı, Şenol (Frontiers in Psychology, 2025)
Introduction In today’s world, it is of great importance to raise qualified learners whose creative thinking skills and self-efficacy are developed and who can make various choices and take responsibility for their choices as well as implementing them by making their own decisions. In this regard, the study examined the role of gifted students’ self-efficacy (SE) as a mediator on the relationship between autonomous learning (AL) and creative cognition (CC). Methods A proposed conceptual model was tested using a cross-sectional survey design. Based on “convenience sampling,” the study group consisted of 528 gifted secondary school students enrolled in three Science and Arts Centers in Ankara, Türkiye in the 2022–2023 academic year. A two-step Structural equation modelling (SEM) analysis was conducted for data analysis. Results and discussion The findings revealed that AL positively and significantly predicted CC, SE was positively correlated with CC, and both dimensions of AL (Independence of Learning- IoL and Study habits- SH) had a significant direct and indirect influence on CC via SE, confirming that the dimensions of AL (IoL and SH) had distinct indirect influences on CC via SE. The study improves our understanding of the role that SE beliefs play in the interaction between AL and CC, which helps to expand and improve models that represent these processes. In order to create conditions that encourage AL, foster SE beliefs, and eventually improve CC among gifted students, educators, policymakers, and parents can create a learning environment that not only promotes AL and strong SH but also fosters SE and CC, ultimately leading to more innovative and self-reliant students.